Innovative Methods of Teaching Foreign Languages - Oripova Kamola Davlatovna (International Journal on Integrated Education, 2022)
The article is the result of practical experience in using demonstration methods of teaching a foreign language where some methods of using computer technologies are shown. The purpose of this article is to review the currently existing innovative technologies and substantiate the feasibility of their practical application in the process of teaching foreign languages in the light of ongoing reforms of the educational system. The article discusses the currently existing innovative teaching technologies (Internet, software, hardware, slide presentations), the possibilities and advantages of their use in the process of teaching foreign languages, which highlights interest from the audience, increases the motivation for studying the subject while this creates a special emotional perception of educational material.